Causes of death and predictors of long-term mortality after pulmonary embolism. (3rd October 2022) - Ebner, M; Eckelt, J; Hobohm, L; Merten, M C; Pagel, C F; Fischer, A S; Lerchbaumer, M H; Stangl, K; Hasenfuss, G; Konstantinides, S V; Schmidtmann, I; Lankeit, M
Abstract: Background: While a large number of studies has investigated short-term outcome after pulmonary embolism (PE), the effects of PE on long-term mortality are insufficiently studied. Purpose: To investigate long-term outcomes in an unselected real-world cohort of patients with acute PE. Methods: Consecutive patients with acute PE enrolled in a prospective single-centre registry between 05/2005 and 12/2017 were followed for up to 14 years. The primary study outcome was all-cause mortality during follow-up. Kaplan-Meier analyses were used to evaluate the probability of long-term survival. The prognostic relevance of baseline characteristics was assessed using Cox proportional hazards models. Standardised mortality rates (SMR) were calculated to estimate relative rates of mortality in the study cohort compared to the expected mortality in the general population adjusted for sex, age and year of birth. Results: We analysed data from 882 patients (age 69 [interquartile range (IQR) 56–77] years), followed for a total of 3, 904 patient years (median follow-up 3.2 [IQR 1.3–7.2] years). Overall, 40.9% of patients died during follow-up. One- and five-year mortality rates were 19.8% and 33.7%, respectively. While most early deaths could be attributed to PE or associated complications, cancer was the predominant cause of death between 30 days and 3 years after PE, whereas cardiovascular events and infections were the most frequent causes of death after more than 3 years (Figure 1). In patients who survived the first 30 days after PE, the observed number of deaths was higher than the expected mortality in the general population throughout the follow-up period (Figure 2; 5-year SMR 2.77 [95% CI 2.42–3.15]). The strongest predictor of late mortality was active cancer at the time of PE, that was associated with a Hazard Ratio [HR] of 4.03 [95% CI 3.07–5.28]) for death after >30 days. Of note, active cancer was only associated with an increased mortality risk during the first three years of follow-up, but did not predict death after more than three years. In non-cancer patients, mortality was also elevated compared to the general population (5-year SMR 1.80 [95% CI 1.51–2.14]) and late mortality was predicted by chronic pulmonary disease (HR 2.22 [95% CI 1.51–3.27]), chronic heart failure (HR 1.90 [95% CI 1.36–2.66]), age per decade (HR 1.79 [95% CI 1.54–2.09]) and anaemia (HR 1.59 [95% CI 1.16–2.17]). Conclusion: Even after survival of the acute phase, the mortality risk of PE patients remained elevated compared to the general population throughout the 14 year follow-up period. The main driver of late mortality is cancer. However, elevated mortality was also observed in in PE patients without cancer, in whom late mortality was predicted by chronic cardiopulmonary comorbidities, age and anaemia. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study was supported by the German Federal Ministry of Education and Research (BMBF 01EO1503).